Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - McLean, Dianne L.; Parsons, Miles J. G.; Gates, Andrew R.; Benfield, Mark C.; Bond, Todd; Booth, David J.; Bunce, Michael; Fowler, Ashley M.; Harvey, Euan S.; Macreadie, Peter I.; Pattiaratchi, Charitha B.; Rouse, Sally; et al. (Frontiers in Marine Science, 2020)
Remotely-operated vehicles (ROVs) are used extensively by the offshore oil and gas and renewables industries for inspection, maintenance, and repair of their infrastructure. With thousands of subsea structures monitored across the world’s oceans from the shallows to depths greater than 1000 m, there is a great and underutilised opportunity for their scientific use. Through slight modifications of ROV operations, and by augmenting industry workclass ROVs with a range of scientific equipment, industry can fuel scientific discoveries, contribute to an understanding of the impact of artificial structures in our oceans, and collect biotic and abiotic data to support our understanding of how oceans and marine life are changing. Here, we identify and describe operationally-feasible methods to alter adjust the way in which industry ROVs are operated to enhance the scientific value of data that they collect, without significantly impacting scheduling or adding to deployment costs. These include: rapid marine life survey protocols, imaging improvements, the addition of a range of scientific sensors, and collection of biological samples. By partnering with qualified and experienced research scientists, industry can improve the quality of their ROV-derived data, allowing the data to be analysed robustly. Small changes by industry now could provide substantial benefits to scientific research in the long-term and improve the quality of scientific data in existence once the structures require decommissioning. Such changes also have the potential to enhance industry’s environmental stewardship by improving their environmental management and facilitating more informed engagement with a range of external stakeholders, including regulators and the public.